Effects of propofol on cortico-cortical evoked potentials in the dorsal language white matter pathway. Issue 8 (August 2021) - Yamao, Yukihiro; Matsumoto, Riki; Kunieda, Takeharu; Nakae, Takuro; Nishida, Sei; Inano, Rika; Shibata, Sumiya; Kikuchi, Takayuki; Arakawa, Yoshiki; Yoshida, Kazumichi; Ikeda, Akio; Miyamoto, Susumu
Highlights: The distribution of large cortico-cortical evoked potentials (CCEP) response was marginally affected by anesthesia. The CCEP N1 amplitude increased from general anesthesia to awaking. CCEP allows testing of the dorsal language white matter pathway even under general anesthesia. Abstract: Objective: In order to evaluate the clinical utility even under general anesthesia, the present study aimed to clarify the effect of anesthesia on the cortico–cortical evoked potentials (CCEPs). Methods: We analyzed 14 patients' data in monitoring the integrity of the dorsal language pathway by using CCEPs both under general anesthesia with propofol and remifentanil and awake condition, with the main aim of clarifying the effect of anesthesia on the distribution and waveform of CCEPs. Results: The distribution of larger CCEP response sites, including the locus of the maximum CCEP response site, was marginally affected by anesthesia. With regard to similarity of waveforms, the mean waveform correlation coefficient indicated a strong agreement. CCEP N1 amplitude increased by an average of 25.8% from general anesthesia to waking, except three patients. CCEP N1 latencies had no correlation in changes between the two conditions. Conclusions: We demonstrated that the distribution of larger CCEP responses was marginally affected by anesthesia and that the CCEP N1 amplitude had tendency to increase from general anesthesia to the awake condition. Significance: The CCEP method provides the efficiency of intraoperative monitoring for dorsal language white matter pathway even under general anesthesia.